Accounting for Data Integrity and Record Governance in Islamic Digital Banking Systems - Prof. Dr. Aijaz Ali Khoso, Prof. Dr. Aijaz Ali Khoso; Dr. Haffezullah Talpur, Dr. Haffezullah Talpur; Dr. Muhammad Shoaib Khan Pathan, Dr. Muhammad Shoaib Khan Pathan (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
Organizations face an undeniably different test in dealing with their business frameworks, as new advances offer extra intricacies and openings because they work. At the core of this developing unsteadiness is the significance of subjective information to give bits of knowledge to settle on these significant choices for the whole venture. Various investigations have shown that numerous associations do not consider their information and that the principal justification this is that they do not need to gauge its quality and esteem as well as assess the expense of incorrect information. This examination gives an incorporated system that associations can embrace as a component of their monetary control and the board cycles to give an instrument to crashes. in any case, distinguish information issues, gauge potential arrangements, and screen continuous expenses and advantages to assist them with improving keep up the nature of their information.